Characterizing distant metastases and survival in oropharyngeal squamous cell carcinoma. Issue 7 (19th March 2021) - Saiyed, Faiez K.; Guo, Theresa; Johnson, Faye; Myers, Jeffrey N.
Abstract: Background: Outcomes of oropharyngeal squamous cell carcinoma (OPSCC) after development of distant metastases (DM) in the context of human papillomavirus (HPV) tumor status remain controversial in the literature. Methods: OPSCC patients with DM treated between June 2015 and March 2019 were included from a prospectively enrolled database. Characteristics of DM including sites, episodes, and timing of disease were analyzed in addition to survival after DM. Results: Sixty‐nine HPV‐positive and 18 HPV‐negative OPSCC patients with DM were included. The 2‐year survival after DM was higher for HPV‐positive patients (54.0% vs. 11.3%, p  < 0.001). HPV‐positive patients did not demonstrate greater episodes or sites of DM. Multiple sites of DM, early development of DM, and Charlson comorbidity Index were independently associated with worse survival after DM. Conclusions: While multiple sites, early DM, and comorbidities were poor prognostic factors, OPSCC patients with distant progression can have substantial survival after DM, including M1 patients.